2021
DOI: 10.1093/nutrit/nuab058
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency and impact on clinical outcomes after kidney transplantation: a systematic review and meta-analysis

Abstract: Context The prevalence of vitamin D deficiency (VDD) and its impact on clinical outcomes after kidney transplant (KT) remain poorly defined. Objectives We conducted a meta-analysis to evaluate the impact of early VDD on clinical outcomes after KT. Data Sources Electronic databases (PubMed, Embase, Web of Science, and The Cochrane Library) were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge this is the first systematic review that summarizes the evidence of the long-term influence of vitamin D deficiency on the outcomes of kidney transplantation. A recent meta-analysis of 28 studies on the same subject by Yin et al [ 32 ] showed that vitamin D deficiency is common following KT and is associated with a high risk of mortality and adverse outcomes including infection and acute rejection. However, this study focused only on early vitamin D deficiency and assessed kidney graft function only one year post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first systematic review that summarizes the evidence of the long-term influence of vitamin D deficiency on the outcomes of kidney transplantation. A recent meta-analysis of 28 studies on the same subject by Yin et al [ 32 ] showed that vitamin D deficiency is common following KT and is associated with a high risk of mortality and adverse outcomes including infection and acute rejection. However, this study focused only on early vitamin D deficiency and assessed kidney graft function only one year post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…As the liver and the kidney play crucial roles in the maintenance of the active vitamin D level, liver and kidney transplant recipients more frequently develop vitamin D deficiency [ 163 , 164 ]. Additionally, these patients have a higher ratio of vitamin D deficiency-associated comorbidities, such as fractures, diabetes, and infections [ 165 , 166 ].…”
Section: Vitamin D and Sirt1 In Relation To Non-communicable Diseases...mentioning
confidence: 99%
“…Following kidney transplantation, the levels of 25(OH)D was decreased especially in early postoperative period. [104][105][106][107][108] Low level of 25(OH)D was associated with increased rate and decreased time to infection of postoperative infection from bacteria, virus (cytomegalovirus and polyomavirus), and fungus. 104,106,108,109 Despite this, in some studies, there was no correlation between infection and levels of 25(OH)D when compared among group of population that separates into groups based on level of 25(OH)D. 85,110 This might be because different cut point of low and high level of 25(OH)D, the infectious prophylaxis strategy and incidence of infection among studies leading to different statistic outcomes.…”
Section: Vitamin D Air Pollution and Effects On Organ Transplantationmentioning
confidence: 99%